Altitudinal influence on diversity and population flux of Drosophilids: Lesser Himalayan region, Garhwal - Kanita K; Rajendra Singh Fartyal; Durga Rawat; Sonali Khali (Environment Conservation Journal)
The present study deals with an investigation of drosophilids population variation and diversity at four stations in the lesser Himalayas (Haridwar, Byasi, Devprayag, and Srinagar) to saturate the knowledge gap in regional biodiversity indicators from 2021 to 2023. The assessment of biodiversity in the Himalayan region poses considerable challenges owing to its complex geography and limited research. To overcome sampling challenges in inaccessible high-altitude regions, these four stations have been adopted for collecting and analyzing the biodiversity of 8047 flies across 29 distinct species using MATLAB. These remarkable results successfully met the objectives of the study. The notable finding includes that the Shannon index values (2.52523, 2.68386, 2.74504, 2.96142) at the sampling sites ​​are within the requisite range [1.5, 3.5] for a typical ecosystem. The lowest Simpson index is 0.02328 at Srinagar, which supports exceptionally high diversity. The study's key findings show that Srinagar has the highest diversity, endorsed by Shannon and Simpson index values. ANOVA analysis in MATLAB confirmed significant differences between group means (p < 0.05), confirmed by box plot analysis.